Representaciones temporales y prácticas sociales: el cambio social a partir de la intervención en el espacio público - Díaz Larrañaga, Nancy; Martin, María Victoria; Ramírez de Castilla, Pilar (Anuario de investigaciones, 2015)
To think and to understand the public space in the current companies, his utopias and tensions it turns out to be a challenge for the investigation in communication. The same thing happens with the perceptions brings over of the time (temporality). The realities and contemporary transformations claim new approaches on the relation between communication, culture and company. The spatial configurations added to the changeable perceptions on the time, need the approximation to practices and subjects to glimpse what happens in the daily life. Following the critical tradition of the communication, we deal to the temporary representations and of the public space as concepts configurators of subjects and groups and, in turn, re-updated, (re) produced or modified in the daily practices